2010
DOI: 10.1111/j.1540-8159.2009.02626.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Fracture Risk of a Small Caliber Implantable Cardioverter Defibrillator Lead

Abstract: In this study, a higher LVEF was associated with a greater risk of lead fracture in patients with Sprint Fidelis 6949 ICD leads. Radiographic features did not predict subsequent risk of lead fracture in our population. (PACE 2010; 437-443).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 13 publications
(29 reference statements)
1
23
3
Order By: Relevance
“…However, the pattern of Fidelis conductor fractures is consistent with a nonrandom time-dependent mechanical failure mode, and it is likely that young active adults with these inherited cardiac diseases mechanically stress Fidelis leads more vigorously than older sedentary patients who have severe ischemic cardiomyopathy and heart failure. The observation that patients who have higher left ventricular ejection fractions also experience higher Fidelis fracture rates 3,5,18 further supports the notion that the Fidelis conductors are vulnerable to normal physiological stresses. The influence of gender is less clear, but women have had a higher early complication rate after de novo ICD implantation than men, 19 and their vascular anatomy may subject leads to the aggressive bend conditions that have been shown to affect Fidelis more than Quattro leads.…”
Section: Discussion Principal Findingssupporting
confidence: 57%
“…However, the pattern of Fidelis conductor fractures is consistent with a nonrandom time-dependent mechanical failure mode, and it is likely that young active adults with these inherited cardiac diseases mechanically stress Fidelis leads more vigorously than older sedentary patients who have severe ischemic cardiomyopathy and heart failure. The observation that patients who have higher left ventricular ejection fractions also experience higher Fidelis fracture rates 3,5,18 further supports the notion that the Fidelis conductors are vulnerable to normal physiological stresses. The influence of gender is less clear, but women have had a higher early complication rate after de novo ICD implantation than men, 19 and their vascular anatomy may subject leads to the aggressive bend conditions that have been shown to affect Fidelis more than Quattro leads.…”
Section: Discussion Principal Findingssupporting
confidence: 57%
“…This study has not confirmed previous findings [21][22][23][24] that patients with confirmed SF lead fracture have statistically significantly higher LVEF, the results obtained herein present contrary results -in our population patients with dysfunctional lead had lower LVEF. Additionally, no statistically significant correlation has been found according to gender www.cardiologyjournal.org [7,9,12,25] or age at implantation [23].…”
Section: Lead Failurecontrasting
confidence: 57%
“…Additionally, no statistically significant correlation has been found according to gender www.cardiologyjournal.org [7,9,12,25] or age at implantation [23]. Neither was any statistical correlation found between the type of prevention (primary vs. secondary), venous access [7,18,21,24,26,27] (cephalic vs. other), nor position of the lead tip in the right ventricle (apex vs. right ventricular outflow track). All parameters were analyzed and were found to be insignificant in multivariate analysis, as well in a univariate analysis.…”
Section: Lead Failurementioning
confidence: 75%
“…This is particularly important because the Fidelis cohort is reaching elective generator replacement. Previous studies have suggested that younger age, 8 -9 female sex, 8 and higher 4,10 or preserved 8 left ventricular ejection fraction predispose to failure. However, previous studies had small sample sizes, incomplete data on potential predictors, or both.…”
Section: Clinical Perspective On P 1225mentioning
confidence: 99%